Genetically modified tumour vaccines - Rossner, P; Bubenik, J; Indrova, M; Sobota, V; Vondrys, P; Zeuthen, J; Jandlova, T; Takac, M (International journal of oncology, 1997)
Two genes, the gene coding for IL-2 and the gene encoding the CD80 molecule, were inserted into murine sarcoma MC12 cells. Tumorigenicity of a variety of cell clones with different expression of the inserted genes was assessed. Most of the genetically manipulated MC12 cell clones were less tumorigenic than the parental MC12 cell population. Tumorigenicity of the clones declined with increasing production of IL-2 as well as with the increasing expression of the CD80 molecule. When the tumorigenicity of the clones carrying an inserted IL-2 gene was compared with that of the clones carrying an inserted CD80 gene, it was found that the insertion of the IL-2 gene suppresses tumorigenicity more efficiently than insertion of the CD80 gene. Admixture of the IL-2-producing MC12 clones to the tumorigenic CD80(+) MC12 cell doses could completely inhibit the tumorigenicity of the CD80(+) cells. Insertion of the CD80 gene into sarcoma cells substantially enhanced the adhesive interaction between the MC12 sarcoma and syngeneic T lymphocytes.